DISTRIBUTION OF ZAKAT IN POVERTY TREATMENT OF MUHAMMADIYAH CITIZENS IN KLATEN DISTRICT (CASE STUDY: LAZISMU REGIONAL LEADER OF MUHAMMADIYAH KLATEN REGENCY) - Basuki Basuki (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2021)
This study aims to determine how zakat distribution in poverty alleviation for Muhammadiyah members of Klaten Regency and how to achieve zakat distribution in poverty alleviation for Muhammadiyah residents of Klaten Regency carried out by Lazismu, Regional Leaders of Muhammadiyah Klaten Regency whether the distribution of zakat been given by Muhammadiyah Klaten residents and the result after being given zakat has improved their welfare or is it still as usual. The methodology used is the descriptive statistical method. This method is used to determine the distribution of zakat in poverty alleviation through observation, interviews, and documentation. This research consists of two data, namely primary data and secondary data, where the primary data is obtained from direct interviews, while secondary data were obtained from distribution report data from the Lazismu Muhammadiyah Regional Leadership, Klaten Regency, and articles or literature related to this study. The results of this study indicate that zakat distribution has been given to Muhammadiyah members of the Klaten Regency, but it has not been able to alleviate poverty. Because zakat funds that are obtained and given to mustahiq can only ease the burden. And that this research will be followed by further research, by conceptualizing zakat distribution using the phenomenological method. The results of this study indicate that zakat distribution has been given to Muhammadiyah citizens of Klaten Regency, but it has not been able to overcome poverty. Because zakat funds that are obtained and given to mustahiq can only ease the burden, and that this research will be followed by further research, by conceptualizing zakat distribution using the phenomenological method. The results of this study indicate that zakat distribution has been given to Muhammadiyah citizens of Klaten Regency, but it has not been able to overcome poverty because zakat funds that are obtained and given to mustahiq can only ease the burden and that this research will be followed by further research, by conceptualizing zakat distribution using the phenomenological method.